Spatial Optimization of Bioenergy Production by Introducing a Cooperative Manure Management System in Bangladesh - Zinat Mahal; Helmut Yabar (Resources)
This study anticipates cooperative manure management as a process for generating bioenergy from livestock manure, thereby reducing greenhouse gas (GHG) emissions in Bangladesh. Therefore, this study’s main objective was to identify clusters for cooperative society development and optimize suitable locations for biogas plant establishment within a cooperative system. Scenarios were explored based on manure types using cluster and network analyses of geographic information systems (GIS). The study observed 13 clusters, which have the potential to produce 6045 million m3 of biogas that can be converted to 9068.64 GWh of electricity yearly. Biogas plants additionally produced 5491.04 kilotons of biofertilizer by reducing GHG emissions estimated to be 10.16 million tons of CO2eq in 2024. This study also optimized 10, 6, and 8 optimum locations for biogas plants according to the scenarios. To implement the findings, this study recommended a coordinated action plan based on the circular economy, which helps to obtain both environmental and economic benefits for a cooperative society. These cooperatives can be implemented for renewable energy production from livestock manure at the community level for sustainable energy generation in Bangladesh.